Ко-эволюционный механизм сбалансированного развития экономических и экологических систем - Половян, А.В. (Економіка промисловості, 2012)
Приведены основные недостатки существующей концепции устойчивого развития, основанной на редукционном подходе. Предлагается дополнить данный вид анализа идеями холизма на основе ко-эволюционного подхода. Рассмотрены особенности ко-эволюции биотической, экологической, социальной и экономической подсистем. Предложена концепция сбалансированного развития, основанная на регулировании процессов совместной эволюции рассмотренных подсистем.
Ключевые слова: сбалансированное развитие, ко-эволюция, холистический подход, экономическая система, экологическая система. Наведено основні недоліки існуючої концепції сталого розвитку, що заснована на редукційному підході. Пропонується доповнити даний вид аналізу ідеями холізму на підставі ко-еволюційного підходу. Розглянуто особливості ко-еволюції біотичної, екологічної, соціальної та економічної підсистем. Запропоновано концепцію збалансованого розвитку, засновану на регулюванні процесів сумісної еволюції розглянутих підсистем.
Ключові слова: збалансований розвиток, ко-еволюція, холістичний підхід, економічна система, екологічна система The article presents the main drawbacks of existing concepts of sustainable development, which is based on the reduction approach. To solve this problem, we propose to add this approach with holistic ideas. Practical implementation of this approach can be based on co-evolution – the mutual development of systems. The features of evolution and co-evolution of biotic, environmental, social and economic subsystems are described. The evolution of the economic subsystems is proposed to be described with the productive forces, production relations and the global value chains. The mechanism of co-evolution of the above subsystems is offered. The concept of sustainable development is offered, which is based on the regulation of co-evolution of subsystems under consideration.
Keywords: sustainable development, co-evolution, holistic approach, economic system, ecological system.